Current Opinions on Surgical Treatment of Fractures of the Condylar Head. Issue 2 (June 2014) - Boffano, Paolo; Benech, Rodolfo; Gallesio, Cesare; Arcuri, Francesco; Benech, Arnaldo
Treatment of mandibular condyle fractures is still controversial, with surgical treatment slowly becoming the preferred option. However, fractures of the condylar head (diacapitular fractures) are still treated conservatively at many institutions. Recently, more and more surgeons have begun to perform open treatment for diacapitular fractures because it allows to restore the anatomical position of the fragments and disc, it allows an immediate functional movement of the jaw, and avoid the ankylosis of the temporomandibular joint induced by the trauma. Several techniques have been proposed to reduce and fix fractures of the condylar head, such as standard bone screws, resorbable screws, resorbable pins, and cannulated lag screws. Therefore, the aim of this article is to review the literature about the surgical treatment of fractures of the condylar head to resume the current knowledge about open treatment of such fractures.